2019
DOI: 10.3389/fphys.2019.00388
|View full text |Cite
|
Sign up to set email alerts
|

A YWHAZ Variant Associated With Cardiofaciocutaneous Syndrome Activates the RAF-ERK Pathway

Abstract: Cardiofaciocutaneous (CFC) syndrome is a genetic disorder characterized by distinctive facial features, congenital heart defects, and skin abnormalities. Several germline gain-of-function mutations in the RAS/RAF/MEK/ERK pathway are associated with the disease, including KRAS, BRAF, MEK1 , and MEK2 . CFC syndrome thus belongs to a group of disorders known as RASopathies, which are all caused by pathogenic mutations in various genes encoding components of the RAS pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 69 publications
(98 reference statements)
1
19
0
Order By: Relevance
“…Recently, a germline variant in 14-3-3zeta ( YWHAZ ) was identified in a patient with a clinical diagnosis of CFC. Expression of this variant in Xenopus tropicalis increased BRAF and RAF1 binding, ERK phosphorylation and decreased body length, consistent with YWHAZ functioning as a RASopathy gene ( Popov et al, 2019 ).…”
Section: Emerging Rasopathy Genesmentioning
confidence: 60%
“…Recently, a germline variant in 14-3-3zeta ( YWHAZ ) was identified in a patient with a clinical diagnosis of CFC. Expression of this variant in Xenopus tropicalis increased BRAF and RAF1 binding, ERK phosphorylation and decreased body length, consistent with YWHAZ functioning as a RASopathy gene ( Popov et al, 2019 ).…”
Section: Emerging Rasopathy Genesmentioning
confidence: 60%
“…In our proteomics study, we showed that 14-3-3σ is up-regulated when NF1 is deleted in HEK293 cells and that restoration of neurofibromin expression leads to decreased/normalization of expression [19]. 14-3-3 proteins have also been implicated in other Rasopathy phenotypes, including cardio-facio-cutaneous syndrome [20] and Noonan syndrome [21].…”
Section: Introductionmentioning
confidence: 99%
“…YWHAZ, a member of 14-3-3 proteins, is a conserved regulatory protein that maintains multiple types of signals via binding to several partner proteins. The binding of 14-3-3 proteins can lead to conformational changes in their partners, masking specific sequences or structural features in the partner proteins that promote the formation of complex [ 93 ]. No previous data has reported YWHAZ interaction with CFTR.…”
Section: Resultsmentioning
confidence: 99%